Composite conductive member, sample holder, electrostatic chuck device
The composite conductive member addresses impedance and heat issues in electrostatic chuck devices by integrating insulating and conductive materials with controlled particle size, maintaining stable impedance and uniform temperature control.
Patent Information
- Application Number
- JP2021031789
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-01
- Publication Date
- 2025-01-07
- Estimated Expiration
- 2041-03-01
AI Technical Summary
Electrostatic chuck devices with conventional plasma electrodes experience increased impedance and heat generation due to the skin effect, leading to non-uniform temperature and discharge issues, and thermal stress causing peeling of layers.
A composite conductive member with controlled impedance and reduced frequency dependence is created by integrating insulating and conductive materials, with specific particle size and distribution, reducing the influence of skin effect and mutual inductance.
The composite conductive member maintains stable impedance across higher frequencies, reducing heat generation and ensuring uniform temperature control, thus enhancing the performance of electrostatic chuck devices.
Smart Images

Figure 0007608871000003 
Figure 0007608871000004 
Figure 0007608871000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a composite conductive member, a sample holder, and an electrostatic chuck device. [Background technology]
[0002] In semiconductor manufacturing equipment and the like, an internal electrode for generating plasma and a power supply terminal are provided inside a ceramic member such as a sample holder. In the sample holder, a plate-like sample such as a semiconductor wafer is placed on the mounting surface, and high-frequency power is applied to the internal electrode, thereby making it possible to process the plate-like sample. The sample holder may also have a configuration in which an electrostatic chuck portion is provided on the mounting surface thereof.
[0003] As the internal electrodes, for example, a composite sintered body containing a matrix phase containing aluminum oxide and a dispersed phase containing molybdenum, carbon, and silicon is used (see, for example, Patent Document 1). In Patent Document 1, the dispersed phase that becomes the conductive path in the composite sintered body is enlarged to reduce the electrical resistance. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] International Publication No. 2019 / 182104 Summary of the Invention [Problem to be solved by the invention]
[0005] Conventional electrostatic chuck devices with plasma electrode functions are significantly affected by the skin effect (a phenomenon in which current does not easily flow through the center of a conductor at high frequencies due to the influence of mutual inductance), and as a result, the impedance of the electrode layer that becomes a plasma electrode at high frequencies and the power supply terminals that transmit voltage to the electrode layer become large, resulting in large heat generation. This heat generation causes problems such as a loss of uniformity in temperature on the mounting surface of the electrostatic chuck member and a tendency for discharge to occur when a voltage is applied to the electrostatic chuck member. In addition, the dielectric material that constitutes the electrostatic chuck member thermally expands. This thermal expansion causes thermal stress, which causes a problem of peeling off the layers that constitute the electrostatic chuck member.
[0006] The present invention has been made in consideration of the above circumstances, and has an object to provide a composite conductive member that experiences less change in impedance up to higher frequencies than conventional ones, a sample holder that is made of the composite conductive member and has a conductive layer or the like for applying an alternating current, and an electrostatic chuck device that includes an electrostatic chuck member made of the sample holder. [Means for solving the problem]
[0007] In order to solve the above problems, one aspect of the present invention provides a composite conductive member comprising an insulating material and a conductive material, and which is made of the insulating material, and when the impedance at both ends of a test piece having a diameter of 10 mm or more is measured, the impedance measured at 100 kHz is between 0.2 and 5 times the impedance measured at 100 Hz.
[0008] In one aspect of the present invention, the impedance of the test piece measured at 100 kHz may be 1 to 5 times the impedance measured at 100 Hz.
[0009] In one aspect of the present invention, the conductive material may have a particle size of 20 μm or less.
[0010] One aspect of the present invention provides a sample holder comprising a ceramic member having a placement surface for placing a sample, an internal electrode layer provided inside the ceramic member, and a power supply terminal provided on a surface of the internal electrode layer opposite to the placement surface, wherein at least one of the internal electrode layer and the power supply terminal is composed of a composite conductive member according to one aspect of the present invention.
[0011] In one aspect of the present invention, the thickness of the internal electrode layer may be 50 μm or more.
[0012] In one aspect of the present invention, when the distance between the lower surface in the thickness direction of the internal electrode layer and the surface of the ceramic member opposite to the placement surface is d2, and the distance between the lower surface in the thickness direction of the internal electrode layer and the lower surface in the thickness direction of the power supply terminal is d3, 1 / 2d2 < d3 ≦ d2 may be satisfied.
[0013] One aspect of the present invention provides an electrostatic chuck device in which an electrostatic chuck member and a temperature adjustment base member are joined via an adhesive layer, wherein the electrostatic chuck member is composed of the sample holder according to one aspect of the present invention.
Advantages of the Invention
[0014] According to the present invention, it is possible to provide a composite conductive member with less change in impedance up to a higher frequency than conventional ones, a sample holder including a conductive layer or the like composed of the composite conductive member, and an electrostatic chuck device including an electrostatic chuck member composed of the sample holder.
Brief Description of the Drawings
[0015] [Figure 1] It is a cross-sectional view showing a sample holder according to an embodiment of the present invention. [Diagram 2] It is a cross-sectional view showing an electrostatic chuck device according to an embodiment of the present invention.
Modes for Carrying Out the Invention
[0016] An embodiment of the composite conductive member, the sample holder, and the electrostatic chuck device of the present invention will be described. It should be noted that the present embodiment is specifically described to allow a better understanding of the gist of the invention, and does not limit the present invention unless otherwise specified.
[0017] <Composite conductive material> A composite conductive member according to one embodiment of the present invention includes an insulating material and a conductive material. The composite conductive member of the present embodiment is Composite conductive material When the impedance at both ends of a test piece having a diameter of 10 mm or more is measured, the impedance measured at 100 kHz is 0.2 to 5 times, preferably 1 to 5 times, and more preferably 1 to 2 times, of the impedance measured at 100 Hz. If the impedance measured at 100 kHz is less than 0.2 times the impedance measured at 100 Hz, the phase of the high frequency wave that generates plasma is shifted, making it difficult to operate a semiconductor manufacturing device using an electrostatic chuck normally. If the impedance measured at 100 kHz is more than 5 times the impedance measured at 100 Hz, the change in heat generation by the electrostatic chuck due to the frequency becomes large, making it impossible to properly control the temperature of the electrostatic chuck.
[0018] The impedance of the test piece can be measured by a method generally used for measuring the dielectric constant of ceramic materials, in which a disk-shaped test piece is clamped between electrodes. The diameter of the test piece should be larger than the cross-sectional area of the surface through which the current flows when the test piece is used as an electrode layer. However, when the test piece is used as an electrode material for a sample holder, the diameter of the power supply terminal of the sample holder in the conduction direction is at most about 10 mm. Therefore, a test piece with a diameter of 10 mm or more should be used. For example, a disk-shaped test piece with a thickness of 3 mm and a diameter of 28 mm in a plan view can be used, and the impedance between both sides of the test piece can be measured using an electrode with a diameter of 13 mm. The skin effect increases the impedance, and the larger the cross-sectional area through which the current flows in the conductor, the greater the impact. Therefore, if the diameter of the test piece is such that the area through which the current flows in the test piece is larger than the cross-sectional area through which the current flows when the test piece is used as an electrode layer, it can be confirmed that the composite conductive member can be used as a sample holder that is less affected by changes in impedance due to frequency, even when used as a power supply terminal or internal electrode layer of a sample holder. The impedance may be measured by incorporating the composite conductive member into a sample holder member or the like as an internal electrode layer and / or a power supply terminal, and then applying a voltage under conditions similar to those in which the sample holder is actually used, to measure the change in impedance with frequency. Since the composite conductive member of the present embodiment is used for purposes other than the internal electrode layers, its shape is not limited to a disk shape in plan view.
[0019] The DC resistance of the above test piece is 10×10 -3 It is preferable that the resistance is Ω·cm or less, and 1×10 -3 It is more preferable that the resistance is less than 0.5×10 -3 It is more preferable that the resistivity is Ω·cm or less. By making the direct current resistance value below this value, a composite conductive sintered body that generates little heat due to current is obtained. The volume resistivity can be measured by a method conforming to JIS K 7194.
[0020] The test piece is a composite conductive part according to the present embodiment. Materials and The composition is the same.
[0021] The composite conductive member of the present embodiment is a molded body or sintered body in which an insulating material and a conductive material are integrated, and has a structure in which the insulating material and the conductive material are composited.
[0022] In the composite conductive member of this embodiment, the conductive paths formed within the composite conductive member are made thinner, thereby reducing the influence of the skin effect of each conductive path. In addition, in the composite conductive member of this embodiment, the conductive paths are folded in various directions within the composite conductive member, thereby reducing the influence of mutual inductance between the conductive paths. Furthermore, in the composite conductive member of this embodiment, the conductive particles that do not contribute to conductivity and do not form conductive paths are reduced, thereby reducing the components that act as capacitors on the reactance of the composite conductive sintered body.
[0023] In the composite conductive member of the present embodiment, the amount of the conductive material in the total volume is preferably 10% or more and 70% or less, and more preferably 35% or more and 65% or less, in terms of volume ratio. When the content ratio is equal to or greater than the lower limit value, the proportion of conductive particles that do not contribute to conduction, which exist in an independent state without contacting each other in the insulating material, increases. The impedance becomes high even in the low frequency range, and the material cannot be used as a conductive material. In addition, when the proportion of particles that do not contribute to conduction increases, the components that act as a capacitor when high frequency is applied increase, which affects the phase of the high frequency and makes it difficult to control the plasma. When the content ratio is equal to or less than the upper limit value, the area of the conductive material that is independent and surrounded by the insulating material in any cross section becomes large, making it difficult to obtain the effect of reducing the effect of the skin effect. By setting the amount of the conductive material within the above range, the path of the conductive path in the composite conductive member becomes complex, the direction of the current flow becomes unstable, and the effect of reducing the effect of the mutual inductance between the conductive paths is easily obtained. Therefore, the change in impedance due to frequency can be reduced.
[0024] [Conductive materials] Examples of the conductive material include conductive ceramics, carbon (C), high melting point metals, and mixtures or compounds thereof. The conductive ceramics are not particularly limited, but examples thereof include silicon carbide (SiC), titanium oxide (TiO2), titanium nitride (TiN), titanium carbide (TiC), tungsten carbide (WC), molybdenum carbide (Mo2C), tantalum (Ta), tantalum carbide (TaC, Ta4C5), etc. Examples of carbon (C) include carbon black, carbon nanotubes, carbon nanofibers, fullerenes, etc. Examples of high melting point metals include tungsten (W), molybdenum (Mo), tantalum (Ta), niobium (Nb), etc.
[0025] By controlling the particle size of the dispersed phase region that is independent and surrounded by the matrix phase of the conductive material, it is possible to obtain a conductive material in which the change in impedance due to frequency is small. The particle size of the conductive material is preferably such that the maximum Feret diameter is 20 μm or less, more preferably 15 μm or less. The Feret diameter D10 is preferably 4.5 μm or less, more preferably 4.0 μm or less, and even more preferably 3.0 μm or less. The Feret diameter D50 is preferably 10 μm or less. The Feret diameter D90 is preferably 15 μm or less, more preferably 10 μm or less. By making the Feret diameter equal to or less than the above lower limit, the thickness of the conductive path is reduced, and the effect of reducing the influence of the skin effect is obtained. The ratio of the Feret diameter D90 to the Feret diameter D10 (D90 / D10) is preferably 5 or less, more preferably 4 or less, and even more preferably 3.5 or less. If the ratio (D90 / D10) is 4 or less, the variation in particle size of the conductive material is reduced, so that the particles that do not contribute to conductivity can be reduced, and the resistance value in direct current can be reduced. In addition, the components that act as a capacitor when high frequency is applied can be reduced. The Feret diameter can be measured from an image (SEM image) of the cross section of the composite conductive member observed by SEM. It is preferable to measure the size by binarizing the SEM image to clarify the boundary of the area to be measured. For the basic operation of the measurement, it is preferable to use a method that complies with the method described in JIS Z8827-1 "Particle size analysis - Image analysis method - Part 1: Static image analysis method".
[0026] [Insulating materials] Examples of insulating materials include insulating ceramics, glass, plastic, and silicone. The insulating ceramics are not particularly limited, but examples thereof include aluminum oxide (Al2O3), aluminum nitride (AlN), silicon nitride (Si3N4), yttrium oxide (Y2O3), yttrium aluminum garnet (YAG), samarium aluminum oxide (SmAlO3), magnesium oxide (MgO), and silicon oxide (SiO2).
[0027] In addition, when the composite conductive member of this embodiment is used as an internal electrode layer of a sample holder, the insulating material is preferably the same as the main component of the sample holder that is in contact with the internal electrode layer. By using the insulating material as the main component of the sample holder that is in contact with the internal electrode layer, the bonding strength between the sample holder and the internal electrode layer is increased, and the sample holder can be made highly reliable.
[0028] A method for producing the composite conductive member of this embodiment will be described. The conductive composite member is formed by mixing raw powder of a conductive material with raw powder of an insulating material, and molding or sintering the mixture to form a composite body in which the conductive material and the insulating material are integrated.
[0029] In order to set the particle size of the conductive material within the above range, it is preferable to use a raw powder of the conductive material that is 5 μm or less, more preferably 2 μm or less, and most preferably 1 μm or less. By setting the particle size of the raw powder to the above value or less, the conductive path is easily thinned, and it is easy to obtain a composite conductive member with a small frequency dependency of impedance. In addition, it is preferable to select the raw powder of the conductive material that is easily dispersed in a solvent by the dispersion treatment described later, and it is preferable that the raw powder of the conductive material is a material that can be mixed uniformly when mixed with the raw powder of the insulating material. The ease of dispersion of the raw powder of the conductive material in a solvent and whether it is a material that can be mixed uniformly when mixed with the raw powder of the insulating material can be evaluated by checking the particle size of the conductive material in the obtained composite conductive member.
[0030] When an insulating ceramic is used as the insulating material, the particle size of the raw powder of the insulating ceramic is preferably 10 times or less than the particle size of the raw powder of the conductive material. By setting the particle size of the raw powder of the insulating ceramic to the above value or less, the raw powder of the insulating ceramic and the raw powder of the conductive material can be mixed uniformly, making it easier to obtain a composite conductive member with small frequency dependence of impedance.
[0031] When mixing the raw powder of the conductive material with the raw powder of the insulating material, it is preferable to disperse the raw powder of the conductive material uniformly. Therefore, the raw powder of the conductive member is dispersed in a dispersion medium and then mixed with the raw insulating material. In order to improve the dispersion of the raw powder of the conductive material during this dispersion, dispersants and surface treatment agents are added. In addition, to disperse the raw powder, equipment with strong dispersing and crushing power such as a bead mill or planetary ball mill is used.
[0032] The conductive material raw powder and the insulating material raw powder dispersed in the dispersion medium are mixed, and a dispersion process is further performed using a disperser. The dispersion liquid containing the conductive material raw powder and the insulating material raw powder uniformly mixed in the dispersion medium is dried to remove the dispersion medium, thereby obtaining a raw powder of the composite conductive member in which the conductive material raw powder and the insulating material raw powder are uniformly mixed.
[0033] In the case where the insulating member is an insulating ceramic, the composite conductive member is obtained by molding the raw material powder of the composite conductive member and then sintering it. As a molding method, a known method such as pressure molding or green sheet molding can be used. When the composite conductive member of this embodiment is used as an internal electrode layer of a sample holder, an internal electrode forming paste for screen printing is prepared using the raw material powder of the composite conductive member, and the internal electrode layer is obtained by applying the paste to a plate-shaped member that will become the sample holder and then sintering it. To prepare the internal electrode forming paste, terpineol or the like can be used as a solvent. A binder such as ethyl cellulose, polymethyl methacrylate, or polyvinyl butyral may be further added to the internal electrode forming paste.
[0034] The raw material powder of the composite conductive member is dried before sintering in order to volatilize the dispersant, the solvent contained in the internal electrode forming paste, the binder, and the like, and then sintered.
[0035] The composite conductive member is sintered by hot pressing (uniaxial pressure sintering). It is preferable to heat the composite conductive member without applying pressure until it reaches 800°C. By heating up to 800°C without applying pressure, it is possible to sufficiently remove volatile components remaining in the raw powder of the composite conductive member. In addition, the pressure during sintering is preferably 5 MPa or more at a temperature of 1000°C or more, more preferably 10 MPa or more, and even more preferably 15 MPa or more. This is because by increasing the pressure during sintering, it is possible to prevent multiple conductive materials from sintering and increasing the particle size, and it is possible to reduce the particle size of the conductive material. The sintering temperature is preferably as low as possible within a temperature range in which the composite conductive member can be sintered sufficiently, and for example, when aluminum oxide is used as the insulating material, the sintering temperature is preferably 1500°C to 1800°C, and more preferably 1600°C to 1700°C. If the sintering temperature is below the lower limit, the conductive material cannot be sintered sufficiently. If the sintering temperature exceeds the upper limit, the conductive material is sintered more and the particle size of the conductive material becomes larger.
[0036] According to the composite conductive member of this embodiment, when the impedance at both ends of a test piece having a diameter of 10 mm or more is measured, the impedance measured at 100 kHz is 0.2 to 5 times the impedance measured at 100 Hz, so that the impedance change is small up to a higher frequency than in the past. Therefore, even when a high-frequency current of 100 kHz or more is applied, the impedance can be prevented from increasing. As a result, heat generation can be suppressed.
[0037] <Sample holder> A sample holder according to one embodiment of the present invention comprises a ceramic member having a mounting surface on which a sample is placed, an internal electrode layer provided inside the ceramic member, and a power supply terminal provided on the surface of the ceramic member opposite the mounting surface for applying a voltage to the internal electrode layer.
[0038] The sample holder of this embodiment will be specifically described below with reference to Fig. 1. Fig. 1 is a cross-sectional view showing the sample holder of this embodiment. In addition, in all the following drawings, the dimensions and proportions of each component have been appropriately changed to make the drawings easier to understand.
[0039] The sample holder of this embodiment shown in FIG. 1 may be, for example, a sample holder used in the manufacturing process of semiconductors or liquid crystal display devices. 1, the sample holder 1 of this embodiment has a mounting plate 2 made of ceramics, the upper surface of which is a mounting surface 2a on which a plate-shaped sample such as a semiconductor wafer is placed, a support plate 3 made of ceramics provided on the surface of the mounting plate 2 opposite the mounting surface 2a, an internal electrode layer 4 sandwiched between the mounting plate 2 and the support plate 3, and a power supply terminal 5 provided on a surface (lower surface) 4b of the internal electrode layer 4 opposite the mounting surface 2a. The sample holder 1 of this embodiment also has a ring-shaped insulating material 6 surrounding the periphery of the internal electrode layer 4. The support plate 3 has a fixing hole 7 formed therethrough in the thickness direction. The outer periphery of the power supply terminal 5 and the fixing hole 7 are joined by sintering. In addition, the upper surface 5a of the power supply terminal 5 in the thickness direction and the lower surface 4b of the internal electrode layer 4 are joined by sintering. In the following description, the side of the mounting surface 2a of the mounting plate 2 will be referred to as "upper" and the side of the support plate 3 as "lower" to indicate the relative positions of each component.
[0040] When the sample holder 1 is used as an electrostatic chuck, an internal electrode layer for electrostatic attraction for electrostatically attracting a sample may be built into the mounting plate 2 in addition to the internal electrode layer 4. When the sample holder 1 is used as a heating device, a heater electrode layer for heating may be built into the mounting plate 2 or the support plate 3. When an electrostatic attraction electrode or a heater electrode layer is built into the sample holder 1, a power supply terminal for applying a voltage to the electrostatic attraction electrode layer or the heater electrode layer can be provided separately.
[0041] In the sample holder 1 of this embodiment, a laminate made up of the mounting plate 2 and the support plate 3 is a ceramic member. The internal electrode layer 4 is provided inside the laminate made up of the mounting plate 2 and the support plate 3.
[0042] In the sample holder 1 of this embodiment, at least one of the internal electrode layer 4 and the power supply terminal 5 is made of the composite conductive material of this embodiment. In order to further enhance the effect of suppressing heat generation in the internal electrode layer 4, it is preferable that the internal electrode layer 4 is made of the composite conductive material of this embodiment. Furthermore, if the power supply terminal 5 is made of the composite conductive material of this embodiment, it is possible to suppress the heat generation in the power supply terminal 5 from being transmitted to the internal electrode layer 4.
[0043] In the sample holder 1 of this embodiment, the thickness of the internal electrode layer 4 is preferably 1 μm or more and 100 μm or less, more preferably 5 μm or more and 30 μm or less, both in the center and the outer periphery of the electrode layer. When the thickness of the internal electrode layer 4 is equal to or more than the above lower limit, a sufficient current for generating plasma can be passed. When the thickness of the internal electrode layer is equal to or less than the above upper limit, an increase in manufacturing costs can be suppressed. In addition, the thickness of the internal electrode layer 4 is preferably the same from the center to the outer periphery. The difference between the maximum and minimum thicknesses in the plane is preferably 10 μm or less, more preferably 6 μm or less. By making the thickness of the internal electrode layer 4 constant in the plane, the heat transfer in the vertical direction in the mounting surface 2a becomes uniform in the plane, so that the sample holder 1 has excellent thermal uniformity. In addition, when the internal electrode layer 4 and the mounting plate 2 are sintered, the pressure applied to the internal electrode layer 4 becomes constant, so that the frequency dependency of the impedance of the internal electrode layer 4 becomes uniform in the plane. Therefore, the controllability of the plasma is improved. In addition, the manufacturing process is simplified.
[0044] The diameter of the power supply terminal 5 is preferably 3 mm or more and 10 mm or less, and more preferably 4 mm or more and 8 mm or less. By setting the diameter of the power supply terminal 5 within this range, it is possible to suppress deterioration of the thermal uniformity of the electrostatic chuck due to the presence of the power supply terminal 5, and to allow a sufficient flow of high-frequency current for generating plasma.
[0045] In the sample holder 1 of the present embodiment, when the distance between the upper surface 5a of the power supply terminal 5 and the placement surface 2a of the placement plate 2 is d1, the distance between the lower surface 4b of the internal electrode layer 4 and the surface (lower surface) 3b of the support plate 3 on the side opposite to the placement surface 2a is d2, and the distance between the lower surface 4b of the internal electrode layer 4 and the lower surface 5b in the thickness direction of the power supply terminal 5 is d3, it is preferable to satisfy 1 / 2d2 < d3 ≤ d2, more preferably to satisfy 3 / 4d2 < d3 ≤ d2, and most preferably d3 = d2. By setting the distance d3 within this range, heat transfer between the power supply terminal 5 and the placement plate 2 can be sufficiently performed, so that the sample holder 1 has excellent heat uniformity also around the power supply terminal 5. Further, in order to connect an electrode for connecting to an external power source to the support plate 3 centering on the power supply terminal 5, the support plate 3 may be perforated. In that case, the distance d2 is set to the value at the non-perforated location on the support plate 3. If the values of the distance d2 and the distance d3 are within the above range, heat transfer between the power supply terminal 5 and the placement plate 2 can be sufficiently performed. Also, it is preferable that the distance d1 and the distance d3 satisfy the relationship d1 < d3. Since the heat capacity around the power supply terminal 5 becomes larger than the heat capacity of the placement plate 2 above the power supply terminal 5 when the distance d3 is larger than the distance d1, and further, heat transfer between the power supply terminal 5 and the placement plate 2 can be improved, the sample holder 1 has excellent heat uniformity also around the power supply terminal 5. Note that the distance d2 corresponds to the thickness of the support plate 3. Also, the distance d3 corresponds to the thickness of the power supply terminal 5.
[0046] [Placement plate] The ceramics constituting the placement plate 2 are not particularly limited as long as they are dielectric materials, have mechanical strength, and have durability against corrosive gases and their plasmas. As such ceramics, for example, aluminum oxide (Al2O3) sintered body, aluminum nitride (AlN) sintered body, aluminum oxide (Al2O3)-silicon carbide (SiC) composite sintered body, etc. are preferably used.
[0047] The thickness of the mounting plate 2 is preferably 0.5 mm or more and 5 mm or less, and more preferably 2 mm or more and 3 mm or less. When the thickness of the mounting plate 2 is equal to or more than the lower limit, the mounting plate 2 has excellent voltage resistance. When the thickness of the mounting plate 2 is equal to or less than the upper limit, the heat capacity of the mounting plate 2 is small, so that the temperature of the plate-shaped sample during processing can be made uniform.
[0048] [Support plate] The support plate 3 supports the mounting plate 2 and the internal electrode layers 4 from below.
[0049] The support plate 3 is made of the same ceramic material as that of the mounting plate 2 . The thickness of the support plate 3 is preferably 0.5 mm or more and 5 mm or less, and more preferably 0.5 mm or more and 3 mm or less. When the thickness of the support plate 3 is equal to or more than the lower limit, a sufficient withstand voltage can be ensured. When the thickness of the support plate 3 is equal to or less than the upper limit, the heat capacity of the mounting plate 2 is small, and the temperature of the plate-shaped sample during processing can be made uniform, making it easier to control the temperature of the plate-shaped sample.
[0050] [Internal electrode layer] The internal electrode layer 4 is used to process the substrate placed on the mounting plate 2 by applying a high frequency voltage.
[0051] Suitable materials for forming the internal electrode layer 4 include high melting point metals such as titanium, tungsten, molybdenum, and platinum, carbon materials such as graphite and carbon, and conductive ceramics such as silicon carbide, titanium nitride, and titanium carbide. In the sample holder 1 of this embodiment, as described above, it is preferable that the internal electrode layer 4 is formed of the composite conductive member of this embodiment.
[0052] The internal electrode layer 4 can be easily formed by a film formation method such as a sputtering method or an evaporation method, or a coating method such as a screen printing method. However, it is preferably joined to the mounting plate 2 and the support plate 3 by sintering. By joining the internal electrode layer 4 to the mounting plate 2 and the support plate 3 by sintering, the heat transfer between the internal electrode layer 4 and the mounting plate 2 and the support plate 3 can be improved. Therefore, the sample holder 1 has excellent heat uniformity.
[0053] [Power supply terminal] The power supply terminal 5 is for applying a high-frequency voltage to the internal electrode layer 4. The power supply terminal 5 is provided in a fixing hole 7 formed so as to penetrate the support plate 3 in the thickness direction. The thickness d3 of the power supply terminal 5 is preferably in the range of 1 / 2d2 < d3 ≦ d2 with respect to the thickness d2 of the support plate 3. By setting the thickness d3 of the power supply terminal 5 within this range, sufficient heat transfer can be achieved between the power supply terminal 5 and the mounting plate 2. Therefore, the sample holder 1 also has excellent heat uniformity around the power supply terminal 5.
[0054] The material of the power supply terminal 5 is not particularly limited as long as it is a conductive material with excellent heat resistance. The material of the power supply terminal 5 is preferably one with a thermal expansion coefficient approximated to those of the internal electrode layer 4 and the support plate 3. As the material of the power supply terminal 5, for example, Kovar alloy, metal materials such as niobium (Nb), various conductive ceramics, and composite ceramics of conductive ceramics and insulating ceramics are preferably used. In the sample holder 1 of the present embodiment, as described above, it is preferable that the power supply terminal 5 is composed of the composite conductive member of the present embodiment. The power supply terminal 5 is preferably joined to the fixing hole 7 by sintering. By joining the power supply terminal 5 and the fixing hole 7 by sintering, the heat transfer in the vicinity of the power supply terminal 5 is improved, and the sample holder 1 also has excellent heat uniformity around the power supply terminal 5.
[0055] [Insulating material] The insulating material 6 surrounds the internal electrode layer 4 to protect the internal electrode layer 4 from corrosive gas and its plasma. The insulating material 6 is made of an insulating material having the same composition or the same main component as the mounting plate 2 and the support plate 3. The mounting plate 2 and the support plate 3 are bonded together via the internal electrode layer 4 by the insulating material 6.
[0056] According to the sample holder 1 of this embodiment, at least one of the internal electrode layer 4 and the power supply terminal 5 is made of the composite conductive member of this embodiment, so that it is possible to suppress the impedance of the internal electrode layer 4 and the power supply terminal 5 from increasing even when a high-frequency current of 100 kHz or more is applied to the internal electrode layer 4 and the power supply terminal 5. As a result, it is possible to suppress the heat generation of the internal electrode layer 4 and the power supply terminal 5 due to the application of the high-frequency current.
[0057] <Manufacturing method of sample holder> Hereinafter, a method for manufacturing the sample holder of this embodiment will be described with reference to FIG. The method for manufacturing the sample holder of this embodiment is as follows.
[0058] [First step] A mounting plate and a support plate are prepared. When the sample holder is used as an electrostatic chuck, a support plate incorporating an internal electrode layer for electrostatic adsorption for electrostatically adsorbing a sample is prepared. When the sample holder is used as a heating device, a support plate or a mounting plate incorporating a heater electrode layer for heating is prepared. A known method can be appropriately used as a method for incorporating an internal electrode layer for electrostatic adsorption or a heater electrode layer in the mounting plate and the support plate. For example, a method can be used in which two ceramic plates are prepared, a paste that will become an internal electrode layer for electrostatic adsorption or a heater electrode layer by sintering is applied to one surface of one of the ceramic plates, the surface on which the paste is applied is sandwiched between the two ceramic plates, and the plates are heated by a hot press or the like to be bonded and sintered. When an electrode layer for electrostatic adsorption or a heater electrode layer is provided on the sample holder, or when a through hole needs to be drilled in the sample holder according to the purpose of use, a coating film that will become an insulating layer can be provided in the coating film that will become the electrode layer according to the purpose.
[0059] [Second step] A fixing hole for installing a power supply terminal is drilled in the support plate. The composite conductive member of this embodiment produced by the above-mentioned method is processed into the same shape as the fixing hole. At this time, it is preferable to make the diameter of the composite conductive member smaller than the diameter of the fixing hole by a range of 0.01 mm to 0.1 mm. By making the diameter of the composite conductive member within the above range, the power supply terminal can be well joined to the fixing hole and the internal electrode layer in the fourth step described later. The power supply terminal is inserted into the fixing hole and temporarily fixed in place with tape or the like.
[0060] [Third step] A paste for forming an internal electrode layer is applied to one of the mounting plate or the support plate obtained in the first step to form a coating film for forming an internal electrode layer, and a paste for forming an insulating layer is applied to form a coating film for forming an insulating layer. When the sample holder is provided with an electrode layer for electrostatic adsorption or a heater electrode layer, or when it is necessary to drill a through hole for a gas inlet or other purpose, a coating film that serves as an insulating layer can be provided in the coating film that serves as the electrode layer depending on the purpose. In the method for producing the sample holder of this embodiment, at least one of the internal electrode layer forming paste and the power supply terminal contains the composite conductive member of this embodiment.
[0061] [Fourth step] The mounting plate and the support plate are sandwiched so that the surfaces on which the coating film for forming the internal electrode layer and the coating film for forming the insulating layer are formed face inward, and are placed in a hot press device. When the mounting plate and the support plate are placed, the tape or the like used to temporarily fix the power supply terminals to the fixing holes is peeled off. The hot press apparatus is pressurized and heated to integrate the mounting plate, the support, the electrode layer, and the power supply terminal. The hot press conditions such as temperature, pressure, and atmosphere can be the same as those used for sintering the composite conductive member described above. The surface of the obtained member is ground to give a desired shape, thereby obtaining the sample holder of this embodiment.
[0062] <Electrostatic chuck device> An electrostatic chuck device 100 according to one embodiment of the present invention may be an electrostatic chuck device using a sample holder of the present invention, the sample holder having an electrostatic attraction electrode layer built into a mounting plate, and bonded to a temperature adjustment base member and the sample holder of the present invention, the sample holder having an electrostatic attraction electrode layer built into a mounting plate, via an adhesive layer.
[0063] The electrostatic chuck device of this embodiment will be specifically described below with reference to Fig. 2. Fig. 2 is a cross-sectional view showing an electrostatic chuck device having a sample holder of this embodiment. 2, the electrostatic chuck device 100 includes a sample holder 1 having an electrode layer for electrostatic attraction within a support plate, a temperature adjustment base member 30, and an adhesive layer 40 that bonds and integrates the sample holder 1 and the temperature adjustment base member 30. In the electrostatic chuck device 100 of this embodiment, the sample holder 1 is an electrostatic chuck member.
[0064] The internal electrode layer 4 is connected to an external high-frequency power source 61 .
[0065] The mounting plate 2 is composed of a dielectric plate 22, an intermediate plate 23, an internal electrode layer 24 for electrostatic attraction, a power supply terminal 25 for electrostatic attraction, and an insulating material 26.
[0066] The material constituting the dielectric plate 22 may be a known ceramic material used in an electrostatic chuck, and may be the same as the material used in the mounting plate 2. The ceramic material is not particularly limited as long as it is a dielectric material, has mechanical strength, and is resistant to corrosive gas and its plasma. As such a ceramic material, for example, an aluminum oxide (Al2O3) sintered body, an aluminum nitride (AlN) sintered body, an aluminum oxide (Al2O3)-silicon carbide (SiC) composite sintered body, etc. are preferably used. As the ceramic material, an aluminum oxide (Al2O3)-silicon carbide (SiC) composite sintered body is particularly preferable.
[0067] The thickness of the dielectric plate 22 is preferably 0.2 mm or more and 0.7 mm or less, and more preferably 0.3 mm or more and 0.6 mm or less. When the thickness of the dielectric plate 22 is equal to or more than the lower limit, the dielectric plate 22 has excellent voltage resistance. When the thickness of the dielectric plate 22 is equal to or less than the upper limit, the electrostatic adsorption force of the sample holder 1 is not reduced, and the thermal conductivity between the plate-shaped sample placed on the mounting surface 2a of the mounting plate 2 and the temperature adjustment base member 30 described later is not reduced, and the temperature of the plate-shaped sample during processing can be kept at a desired constant temperature.
[0068] The material constituting the intermediate plate 23 is preferably a material having the same main component as the dielectric plate 22 , and more preferably the same material as the material constituting the dielectric plate 22 .
[0069] The thickness of the intermediate plate 23 is preferably 0.2 mm or more and 0.7 mm or less, and more preferably 0.3 mm or more and 0.6 mm or less. When the thickness of the intermediate plate 23 is equal to or more than the lower limit, the intermediate plate 23 has excellent voltage resistance. When the thickness of the intermediate plate 23 is equal to or less than the upper limit, the electrostatic adsorption force of the sample holder 1 is not reduced, and the thermal conductivity between the plate-shaped sample placed on the mounting surface 2a of the mounting plate 2 and the temperature adjustment base member 30 described later is not reduced, and the temperature of the plate-shaped sample during processing can be kept at a desired constant temperature.
[0070] Examples of materials constituting the electrostatic attraction internal electrode layer 24 include conductive sintered bodies such as aluminum oxide-tantalum carbide (Al2O3-Ta4C5), aluminum oxide-tungsten (Al2O3-W), aluminum oxide-silicon carbide (Al2O3-SiC), aluminum nitride-tungsten (AlN-W), aluminum nitride-tantalum (AlN-Ta), and yttrium oxide-molybdenum (Y2O3-Mo), as well as high-melting point metals such as tungsten (W), tantalum (Ta), and molybdenum (Mo). In order to reduce dielectric loss of the electrostatic attraction internal electrode layer 24 due to high frequency, it is preferable to use the composite conductive member of the present invention.
[0071] The thickness of the electrostatic attraction internal electrode layer 24 is not particularly limited, but is preferably 5 μm or more and 40 μm or less, and more preferably 20 μm or more and 30 μm or less. When the thickness of the electrostatic attraction internal electrode layer 24 is equal to or more than the lower limit, sufficient conductivity can be ensured. When the thickness of the electrostatic attraction internal electrode layer 24 is equal to or less than the upper limit, cracks are unlikely to occur at the bonding interface between the electrostatic attraction internal electrode layer 24 and the dielectric plate 22 and the intermediate plate 23 due to the difference in thermal expansion between the electrostatic attraction internal electrode layer 24 and the dielectric plate 22 and the intermediate plate 23. The number of electrodes may be single pole or multiple poles depending on the structure of the Coulomb type electrostatic chuck part, the Johnson-Rahbek type electrostatic chuck part, etc.
[0072] The material constituting the electrostatic attraction power supply terminal 25 is not particularly limited as long as it is a conductive material having excellent heat resistance. The material constituting the electrostatic attraction power supply terminal 25 is preferably one having a thermal expansion coefficient close to that of the electrostatic attraction internal electrode layer 24 and the intermediate plate 23. The material constituting the electrostatic attraction power supply terminal 25 is preferably, for example, a metal material such as Kovar alloy or niobium (Nb), various conductive ceramics, or composite ceramics of conductive ceramics and insulating ceramics. In the electrostatic chuck device 100 of this embodiment, the electrostatic attraction power supply terminal 25 is preferably made of the composite conductive member of the present invention.
[0073] In the electrostatic attraction power supply terminal 25, it is preferable that the lower surface 25b in the thickness direction of the electrostatic attraction power supply terminal 25 and the fixing hole 7 adjacent to the electrostatic attraction power supply terminal 25 are joined by sintering. By joining the lower surface 25b of the electrostatic attraction power supply terminal 25 and the fixing hole 7 adjacent to the electrostatic attraction power supply terminal 25 by sintering, heat transfer in the vicinity of the power supply terminal 5 is improved, and the sample holder 1 has excellent thermal uniformity.
[0074] The insulating material 26 is disposed on the outer periphery of the electrostatic attraction internal electrode layer 24, and protects the electrostatic attraction internal electrode layer 24 from corrosive gas and its plasma, and also bonds and integrates the boundary between the dielectric plate 22 and the intermediate plate 23, i.e., the outer periphery region other than the electrostatic attraction internal electrode layer 24. The material constituting the insulating material 26 is an insulating material having the same composition or components as the material constituting the dielectric plate 22 and the intermediate plate 23.
[0075] [Temperature control base material] The temperature adjustment base member 30 is a thick disk-shaped member made of at least one of metal and ceramics. The body of the temperature adjustment base member 30 may also serve as an internal electrode for plasma generation. A flow path (not shown) for circulating a cooling medium such as water, He gas, or N2 gas is formed inside the body of the temperature adjustment base member 30. In addition, a receiving hole 41 is formed in the body of the temperature adjustment base member 30. The receiving hole 41 is connected to the fixing hole 7 of the support plate 3.
[0076] The material constituting the temperature adjusting base member 30 is not particularly limited as long as it is a metal having excellent thermal conductivity, electrical conductivity, and workability, or a composite material containing such a metal. For example, aluminum (Al), copper (Cu), stainless steel (SUS), etc. are preferably used as the material constituting the temperature adjusting base member 30. At least the surface of the temperature adjusting base member 30 exposed to plasma is preferably anodized or resin-coated with polyimide resin. More preferably, the entire surface of the temperature adjusting base member 30 is anodized or resin-coated.
[0077] By subjecting the temperature adjusting base member 30 to anodizing or resin coating, the plasma resistance of the temperature adjusting base member 30 is improved and abnormal discharge is prevented. Therefore, the plasma resistance stability of the temperature adjusting base member 30 is improved and the occurrence of surface scratches on the temperature adjusting base member 30 can be prevented.
[0078] Inside the accommodation hole 41 provided in the base member 30 for temperature adjustment, an insulator 51 made of ceramics is fixed via an adhesive.
[0079] As the material constituting the insulator 51, ceramics that are insulating and have durability against plasma and radicals (free radicals) are preferable. As this ceramics, ceramics composed of one kind selected from aluminum nitride (AlN), aluminum oxide (Al2O3), silicon nitride (Si3N4), zirconium oxide (ZrO2), sialon, boron nitride (BN), silicon carbide (SiC), or composite ceramics containing two or more kinds are preferably used.
[0080] In the insulator 51, a through hole 52 that penetrates the central portion of the insulator 51 in the thickness direction is formed. A power supply connection portion 71 is disposed in the through hole 52 provided in the insulator 51.
[0081] The power supply connection portion 71 is for transmitting the current from the high-frequency power supply 61 to the power supply terminal 5 and the electrostatic adsorption power supply terminal 25. As the material constituting the power supply connection portion 71, materials and shapes with a small amount of heat generation when used as an electrostatic chuck are used. As the material constituting the power supply connection portion 71, for example, a metal stranded wire, a metal mesh wire, a metal tube, a metal bar, etc. can be appropriately used, and those subjected to plating treatment to reduce the surface resistance may also be used.
[0082] The power supply connection portion 71, the power supply terminal 5, and the electrostatic adsorption power supply terminal 25 may be electrically connected by contacting without joining, but it is preferable to join them using a brazing material 81 or the like. In addition, a recess may be provided in the lower surface 5b of the power supply terminal 5 and / or the lower surface 3b in the thickness direction of the support plate 3 during brazing to prevent the brazing material 81 from flowing out during brazing. The recess is preferably provided so that the thickness d3 of the power supply terminal 5 is in the range of 1 / 2d2 < d3 ≦ d2 with respect to the thickness d2 of the support plate. By setting the thickness d3 within this range, heat transfer between the power supply terminal 5 and the mounting plate 2 can be sufficiently performed, so that the sample holder 1 has excellent heat uniformity also around the power supply terminal 5.
[0083] The power supply connection portion 71 may be connected to an external high frequency power supply 61 and a DC power supply 62 for electrostatic attraction.
[0084] [Adhesive layer] The adhesive layer 40 bonds and integrates the sample holder 1 and the temperature adjusting base member 30 together.
[0085] The thickness of the adhesive layer 40 is preferably 50 μm or more and 500 μm or less, and more preferably 100 μm or more and 200 μm or less. If the thickness of the adhesive layer 40 is within the above range, the adhesive strength between the sample holder 1 and the temperature adjustment base member 30 can be sufficiently maintained. Also, the thermal conductivity between the sample holder 1 and the temperature adjustment base member 30 can be sufficiently ensured.
[0086] The adhesive layer 40 is formed of, for example, a hardened body obtained by heat-hardening a silicone-based resin composition, an acrylic resin, an epoxy resin, or the like. A silicone-based resin composition is more preferred because it is a silicon compound having a siloxane bond (Si-O-Si) and is a resin with excellent heat resistance and elasticity.
[0087] As such a silicone-based resin composition, a silicone resin having a heat curing temperature of 70°C to 140°C is particularly preferable. Here, if the heat curing temperature is below 70°C, when the sample holder 1 and the temperature adjusting base member 30 are joined in a facing state, the curing does not proceed sufficiently during the joining process, which is undesirable since it results in poor workability. On the other hand, if the heat curing temperature exceeds 140°C, the thermal expansion difference between the sample holder 1 and the temperature adjusting base member 30 becomes large, which increases the stress between the sample holder 1 and the temperature adjusting base member 30 and may cause peeling between them, which is undesirable.
[0088] According to the electrostatic chuck device 100 of the present embodiment, since the electrostatic chuck member is composed of the sample holder 1, it is possible to suppress the impedance of the internal electrode layer 4 and the power supply terminal 5 from increasing even when a high-frequency current of 100 kHz or more is applied to the internal electrode layer 4 and the power supply terminal 5. As a result, it is possible to suppress the heat generation of the internal electrode layer 4 and the power supply terminal 5 due to the application of the high-frequency current.
[0089] A method for manufacturing the electrostatic chuck device of this embodiment will be described below.
[0090] The sample holder 1 used in the electrostatic chuck device 100 of this embodiment is fabricated in the same manner as in the above-mentioned method for manufacturing the sample holder. Three ceramic plates that serve as the dielectric plate 22, the intermediate plate 23, and the support plate 3 are prepared. A paste that becomes the electrostatic attraction internal electrode layer 24 by sintering is applied to one surface of the intermediate plate 23 on which the electrostatic attraction internal electrode layer 24 is formed. Similarly, a paste that becomes the internal electrode layer 4 by sintering is applied to one surface of the support plate 3 on which the internal electrode layer 4 is formed. Next, the surface coated with the paste that will become the electrostatic attraction internal electrode layer 24 is sandwiched between the dielectric plate 22 and the intermediate plate 23. Also, the surface coated with the paste that will become the internal electrode layer 4 is sandwiched between the intermediate plate 23 and the support plate 3. In this way, a laminate is formed of the dielectric plate 22, the intermediate plate 23, and the support plate 3 laminated with the above-mentioned paste interposed therebetween. Next, the laminate is heated and sintered by a hot press or the like to bond the dielectric plate 22, the intermediate plate 23 and the support plate 3, and also forms an internal electrode layer 24 for electrostatic attraction between the dielectric plate 22 and the intermediate plate 23, and an internal electrode layer 4 between the intermediate plate 23 and the support plate 3. In this way, the sample holder 1 is obtained. Depending on the purpose of use, a coating film serving as an insulating layer may be provided in the coating film serving as the internal electrode layer 4 or the electrostatic attraction internal electrode layer 24 . The conditions of the hot press, such as temperature, pressure, and atmosphere, can be the same as those when sintering the composite conductive member described above.
[0091] The obtained sample holder 1 and the temperature adjustment base member 30 are joined and integrated via an adhesive layer 40 to obtain the electrostatic chuck device 100 of this embodiment.
[0092] In the sample holder 1 and electrostatic chuck device 100 of this embodiment, a number of protrusions for supporting a plate-like sample such as a semiconductor wafer may be provided on the mounting surface 2a of the mounting plate 2 depending on the purpose of use (not shown). Furthermore, a peripheral wall having the same height as the protrusions may be formed on the peripheral portion of the mounting surface 2a of the mounting plate 2 to prevent leakage of a cooling gas such as helium (He) (not shown). In addition, the sample holder 1 and the electrostatic chuck device 100 can be appropriately provided with through holes for flowing helium (He) gas for cooling and through holes for passing lift pins used to transport a plate-shaped sample, etc., using known techniques depending on the purpose of use.
[0093] The plate-like sample according to this embodiment is not limited to a semiconductor wafer, but may be, for example, a glass substrate for a flat panel display (FPD) such as a liquid crystal display (LCD), a plasma display (PDP), or an organic electroluminescence (EL) display. The electrostatic chuck device according to this embodiment may be designed according to the shape and size of the substrate. EXAMPLES
[0094] The present invention will be described in more detail below with reference to examples and comparative examples, but the present invention is not limited to the following examples.
[0095] [Example 1] The starting materials used were aluminum oxide powder (average particle size 0.2 μm, manufactured by Taimei Chemical Industry Co., Ltd.) as the insulating material, and tungsten carbide powder (average particle size 1 μm, manufactured by Nippon Shinkinzoku Co., Ltd.) as the conductive material. Tungsten carbide powder and a polymeric dispersant were added to 2-propanol as a dispersion medium, and the mixture was dispersed for 2 hours in a bead mill using zirconium oxide beads with a diameter of 0.1 mm to obtain a tungsten carbide powder dispersion. Aluminum oxide powder and 2-propanol were added to the obtained tungsten carbide powder dispersion, and mixed for 5 hours using a ball mill using aluminum oxide media with a diameter of 1 mm to 5 mm. The ratio of aluminum oxide powder to tungsten carbide powder was 60 volume % aluminum oxide powder and 40 volume % tungsten carbide powder. The dispersion obtained by mixing in the ball mill was dried to obtain a raw material powder for the composite conductive member. The raw material powder of the composite conductive member was uniaxially press molded at a pressure of 5 MPa using a die molding method to obtain a disk-shaped composite conductive member compact with a diameter of 50 mm and a thickness of 6 mm. The obtained molded body was set in a graphite mold and subjected to pressure sintering. First, the molded body was heated from room temperature to 900°C at a heating rate of 10°C / min in a vacuum atmosphere without applying a pressing pressure. After the heating temperature reached 900°C, it was held for 1 hour, and then, in an argon atmosphere at atmospheric pressure and a pressing pressure of 20 MPa, the temperature was raised to 1650°C at a heating rate of 10°C / min and held for 3 hours to perform sintering, thereby obtaining a composite conductive member of Example 1.
[0096] [Example 2] A composite conductive member of Example 2 was obtained in the same manner as in Example 1, except that tantalum carbide powder (average particle size 1 μm, manufactured by Japan New Metals Co., Ltd.) was used as the raw material for the conductive material.
[0097] [Experimental Example 1] A composite conductive member of Experimental Example 1 was obtained in the same manner as in Example 1, except that molybdenum carbide powder (average particle diameter 1 μm, manufactured by Nippon Shinkinzoku Co., Ltd.) was used as the raw conductive material and dispersion treatment of the raw conductive material was not performed using a bead mill.
[0098] [Comparative Example 1] The composite conductive member of Comparative Example 1 was obtained in the same manner as in Example 1, except that molybdenum carbide powder (average particle diameter 1 μm, manufactured by Nippon Shinkinzoku Co., Ltd.) was used as the raw material for the conductive material, the maximum temperature in the pressure sintering was 1800°C, and the pressing pressure was 10 MPa.
[0099] The production conditions for the composite conductive members in Example 1, Example 2, Experimental Example 1 and Comparative Example 1 are shown in Table 1.
[0100] [Table 1]
[0101] [evaluation] For the composite conductive members of Example 1, Example 2, Experimental Example 1, and Comparative Example 1, the Feret diameter of the conductive particles, the variation in the Feret diameter of the conductive particles, and the impedance were measured.
[0102] "Ferret diameter of conductive particles, variation of Ferret diameter of conductive particles" The Feret diameter of the conductive particles was measured from the image (SEM image) of the cross section of the composite conductive member observed by SEM. The basic operation in the measurement was based on the method described in JIS Z8827-1 "Particle size analysis - Image analysis method - Part 1: Static image analysis method". By the above-mentioned method, the Feret diameters D90 and D10 of the conductive particles were measured, and the ratio of the Feret diameter D90 to the Feret diameter D10 (D90 / D10) was calculated to evaluate the variation in the Feret diameter of the conductive particles. The results are shown in Table 2.
[0103] "Impedance Measurement" For the composite conductive members in Example 1, Example 2, Experimental Example 1, and Comparative Example 1, test pieces with a diameter of 28 mm and a thickness of 3 mm were prepared and the impedance was measured. The diameter of the main electrode of the electrode used in the measurement was 13 mm, and the impedance was measured at 100 Hz, 100 kHz, and 1 MHz. For the measurement, an impedance analyzer E4990A manufactured by Keysight Technologies and a test fixture 16451B electrode type Type D (test piece size: diameter 28 mm, thickness 3 mm, main electrode diameter 13 mm) were used. The value obtained by dividing the impedance at 100 Hz from the impedance at 100 kHz was taken as the impedance change rate at 100 kHz, and the value obtained by dividing the impedance at 100 Hz from the impedance at 1 MHz was taken as the impedance change rate at 100 kHz. The results are shown in Table 2.
[0104] [Table 2]
[0105] The composite conductive members of Examples 1 and 2 had a smaller impedance change rate than the composite conductive members of Experimental Example 1 and Comparative Example 1. This is because the composite conductive members of Examples 1 and 2 had smaller Feret diameters of the conductive particles constituting the composite conductive members than the composite conductive members of Experimental Example 1 and Comparative Example 1. Moreover, the impedance change rate of the composite conductive member of Example 1 was 1 or more, and the impedance change rate of the composite conductive member of Example 2 was 1.9 or less. This is because the composite conductive member of Example 2 had a large variation in Feret diameter (D90 / D10), which increased the proportion of conductive particles that did not contribute to conductivity and increased the components that acted as a capacitor in the reactance of the composite conductive member. [Industrial Applicability]
[0106] As described above, the present invention provides a composite conductive member that has a small impedance change rate and suppresses heat generation even at high frequencies, and the composite conductive member can be used as a sample holder that suppresses heat generation even at high frequencies. In addition, by using the sample holder on the mounting surface, the composite conductive member can be used as an electrostatic chuck device. [Explanation of symbols]
[0107] 1 Sample holder 2. Placement plate 3 Support plate 4 Internal electrode layer 5 Power supply terminal 6. Insulation Materials 7 Fixing hole 22 Dielectric plate 23 Intermediate plate 24 Internal electrode layer for electrostatic adhesion 25 Electrostatic adhesion power supply terminal 26 Insulation Materials 30 Temperature control base material 40 Adhesive layer 41 Receiving hole 51 Insulator 52 Through hole 61 High frequency power supply 62 DC power supply 71 Power connection 81 Brazing material 100 Electrostatic chuck device
Claims
1. A composite conductive member constituting an internal electrode or a power supply terminal of a sample holder, The composite conductive member includes an insulating material and a conductive material, A composite conductive member comprising the composite conductive member, wherein when the impedance at both ends of a test piece having a diameter of 10 mm or more is measured, the impedance measured at 100 kHz is 0.2 to 5 times the impedance measured at 100 Hz.
2. 2. The composite conductive member according to claim 1, wherein the impedance of the test piece measured at 100 kHz is 1 to 5 times the impedance measured at 100 Hz.
3. The composite conductive member according to claim 1 or 2, wherein the particle size of the conductive material is 20 μm or less.
4. a ceramic member having a mounting surface on which a sample is placed, an internal electrode layer provided inside the ceramic member, and a power supply terminal provided on a surface of the internal electrode layer opposite to the mounting surface; A sample holder, wherein at least one of the internal electrode layer and the power supply terminal is made of the composite conductive member according to claim 1 or 2.
5. 5. The sample holder according to claim 4, wherein the internal electrode layer has a thickness of 50 [mu]m or more.
6. 6. The sample holder according to claim 4, wherein, when a distance between a lower surface of the internal electrode layer in a thickness direction and a surface of the ceramic member opposite to the mounting surface is d2, and a distance between a lower surface of the internal electrode layer in the thickness direction and a lower surface of the power supply terminal in the thickness direction is d3, 1 / 2d2<d3≦d2 is satisfied.
7. An electrostatic chuck device comprising an electrostatic chuck member and a temperature adjustment base member bonded together via an adhesive layer, 7. An electrostatic chuck device, wherein the electrostatic chuck member is a sample holder according to claim 4.
Citation Information
Patent Citations
Grounding resistor and method of producing the same
JP2003212657A
Electrostatic chuck member
JP2012178552A
Electrostatic chuck device
JP2015019027A
Electrostatic chuck
JP2020161801A
Electrostatic chuck device and production method for electrostatic chuck device
WO2019182104A1